Safety evaluation of fermented fish and shellfish products III. Heavy metal contaminants - Mabesa, R.C; Atutubo, E.O; Bandian, V.T
Fermented fish and shelfish products from Cebu, Bocolod and Zamboanga cities were analyzed for the presence of lead, cadmium and mercury. Results obtained by atomic absorption spectrophotometry revealed that the samples contained low levels of heavy metals ranging from 0.40 to 0.70 ppm lead, 0.05 to 0.10 ppm cadmium and 0.07 to 0.09 ppm mercury which are below the toxic limits established for these heavy metals